Psychoanalytic Reality of Prose - Todorović, Milorad V. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Scientific methods of a particular field of knowledge can not be freely applied to a different field without any adjustments or reservations. Openness to a different approach is detrimental here. According to Nothrop Frye, psychonalysis in literature tends to “blur the lines between methods”(Frye 1979: 383) thus increasing openness. Therefore, the anxiety that exists between the theory of psychonalysis and the practice of psychoanalytic therapy will follow the application of psychoanalysis to other scientific fields. Solid grasp of the theory of psychoanalysis is incomplete without understanding its practical implementation in the domain of pain as its priviledged source of truth. Even Jacques Lacan emphasized this by distinguishing between understanding and knowing Jacques Derrida’s psychoanalysis. The interdisciplinary activity, valued today as an important aspect of research, cannot be accomplished by simple confrontations between various specialized branches of knowledge. According to Roland Barthes, interdisciplinary work is not a peaceful operation: it begins effectively when the solidarity of the old disciplines breaks downto the benefit of a new object and a new language, neither of which is in the domain of those branches of knowledge that one calmly sought to confront (Barthes 1986b:181). Mirjana Lončar Vujnović proposes, following Barthes logic, to substitute the term psychoanalysis with the term “experimental mysticism” (Lončar Vujnović 2014: 46). Her proposition has no semantic justification (and not only for its failed attempt at oxymoron) let alone scientific.The exploration of the unconscious psyche which is unknown and irrational – designated under certain circumstances as the exploration of the mystical as a hidden, secret part of a man’s soul – was scrutinized in psychoanalysis by employing a rigorous scientific method in reverence to the methods of the natural sciences. Furthermore, due to the nomothetic-ideographic and discursive nature of psyche, psychoanalysis also included the hermeneutic methodpertinent to the research of various symptoms and sintomas, as well asgenesis and telos.